Pengaruh Literasi Keuangan dan Perilaku Keuangan terhadap Pengelolaan Keuangan Ibu Rumah Tangga di Desa Sido Mulyo Kabupaten Tebo - Latifah Oktanavia; Agustina Mutia (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to determine the influence of financial literacy and financial behavior on the financial management of housewives in Sido Mulyo Village, Tebo Regency. The phenomenon shows that many housewives experience difficulties in managing family finances due to a lack of financial understanding and uncertain income. This study used a quantitative approach with a survey method, involving 91 housewives as a sample. Data were collected through questionnaires and analyzed using multiple linear regression techniques with the help of the SmartPLS 4.0 application. The results showed that financial literacy partially had a positive and significant effect on financial management. However, financial behavior did not have a significant effect on housewives' financial management. The conclusion of this study is that the higher the level of financial literacy and financial behavior of housewives, the better their financial management will be. Therefore, increasing financial education and awareness is essential so that housewives can manage family finances more effectively and sustainably.